Hematological and biochemical investigations on the effect of vitamin E and C on Oreochromis niloticus exposed to zinc oxide nanoparticles - Alkaladi, Ali (Saudi J Biol Sci, 2015)
This study was carried out to determine the LC(50) of zinc oxide nanoparticles (ZnONPs) on Oreochromis niloticus and to investigate the effect of vitamin E and C on hematological and biochemical alterations induced by two sublethal concentrations (1 and 2 mg/L) of ZnONPs. One hundred and eighty fish were used for studying the lethal concentrations of ZnONPs. For sublethal study two hundred and twenty-five males of O. niloticus were equally divided into five groups, control, the second and the third were treated with 1 and 2 mg/L ZnONPs respectively. The fourth and fifth were exposed to the same concentrations of ZnONPs plus vitamins E and C. The results revealed that the 96 h LC(50) of ZnONPs was 3.1 ± 0.4 mg/L. The sublethal study revealed the presence of normocytic normochromic anemia in groups (2, 3 and 5) along the experiment period. The 4th group showed normocytic normochromic anemia at the 7th day and microcytic hypochromic anemia at the 15th day. Leukocytosis, heterophilia, lymphopenia and monocytopenia were recorded at the 7th day in all treated groups compared with the normal control. At the 15th day heteropenia, lymphopenia and monocytopenia were reported in all treated groups. A significant increase in the serum levels of alkaline phosphatase, aminotransferases, urea, creatinine and erythrocytic nuclear and morphological abnormalities along the experimental periods in all treated groups compared with the normal control. Serum total protein and albumin levels were significantly decreased at the same period in the same groups. Addition of vitamin E and C to the diet (groups 4 and 5) significantly improved all measured parameters compared with groups (2 and 3) which treated with ZnONPs only.